(untitled) (Research, Society and Development, 2022)
One of the main consequences of anthropogenic activities is the reduction of forest areas and their fragmentation, interfering with gene flow between populations, harming biodiversity conservation and the provision of ecosystem functions. In a landscape composed of remains of Atlantic Forest, this article aims to comprehend its natural vegetation dynamic, supported by the evaluation of its forest structure. Maps of land use and land cover, landscape metrics, and Areas of Permanent Preservation (APPs) were produced. The landscape studied is several fragmented, having forest patches elongates, exposing them to influences from their neighborhood, predominantly agricultural. Several protected areas do not have native vegetation, compromising the water quality and biodiversity, in addition to not follow the legislation. An environmental planning that prioritizes the forest conservation and the compliance with the current legislation is fundamental, aiming to increase forest connectivity and the protection of water resources in front of a predominantly agricultural matrix.